"You can't buy a vote": Meanings of money in a Mumbai election. (November 2014) - BJÖRKMAN, LISA
<x xml:space="preserve">Abstract</x> In Mumbai elections, an influx of money is not leading to the commoditization of the vote. Rather, as ethnographic analysis shows, actors involved with moving money have divergent and sometimes‐conflicting aspirations, motivations, and agendas, within which cash plays multiple roles simultaneously. Election‐time cash flow inhabits a deeply political landscape of contestation where issues at the heart of Mumbai's modernity—land use, infrastructural investment, and business prospects—are negotiated and speculated on. These findings critically engage a conceptual terrain that counterposes individual rationality and political choice to traditional forms of authority mediated by relations of patronage, while producing important insights into long‐standing anthropological debates on money and exchange. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>